2009
DOI: 10.1111/j.1442-2042.2009.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel‐based chemotherapy with zoledronic acid and prednisone in hormone refractory prostate cancer: Factors predicting response and survival

Abstract: Objectives:To evaluate the efficacy of docetaxel/prednisone and zoledronic acid in hormone refractory prostate cancer (HRPC) patients and to analyze prognostic factors predicting overall survival. Methods: Forty-four HRPC patients were given docetaxel (75 mg/m 2 ), prednisone and zoledronic acid (4 mg) every three weeks. Overall and progression-free survival curves were calculated. Using the log-rank test, variables predicting overall survival (age, Gleason score, baseline prostate-specific antigen [PSA], perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The use of zoledronic acid in treating prostate cancer patients is imperatively rational knowing that most of these patients present with skeletal involvement, in addition to the demonstrated antitumor effects of zoledronic acid [9]. Zoledronic acid is the only bisphosphonate that has demonstrated a statistically significant reduction in skeletal morbidity in CRPC patients [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of zoledronic acid in treating prostate cancer patients is imperatively rational knowing that most of these patients present with skeletal involvement, in addition to the demonstrated antitumor effects of zoledronic acid [9]. Zoledronic acid is the only bisphosphonate that has demonstrated a statistically significant reduction in skeletal morbidity in CRPC patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, high-dose calcitriol has shown good response rates in combination with docetaxel [8]. Zoledronic acid, a known bisphosphonate, has antitumor activity, and it has also been used with docetaxel in treating CRPC with good efficacy [9]. …”
Section: Introductionmentioning
confidence: 99%
“…All of them suffered symptomatic bone progression before their death, 40 (75.5 %) in the Group A and 45 (86.5 %) in the Group B. The median overall survival time was 19 months (95 % CI, [16][17][18][19][20][21][22] and 15 months (95 % CI, [12][13][14][15][16][17][18][19], respectively (P = 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, its inclusion into a regular regimen with docetaxel holds a strong case, particularly because its synergistic effects with docetaxel which may result in different mechanism of induction of apoptosis in cancerous cells [20][21][22]. Meanwhile, bisphosphonates also have by themselves shown an improved overall survival advantage when used in CRPC [11][12][13]. Jaw osteonecrosis 0 (0) 0 (0)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation